Modelling the effect of non-planarity on luminescence energy of conjugated polymers - Correia, Helena M. G. (2006)
We present theoretical investigations of structural and electronic properties of ground-state and low-lying excited singlet states in isolated chains of conjugated polymers using a self-consistent quantum molecular dynamics method. With this approach, we have determined the energy of both states as function of the twist angle between two planar segments of the same polymer chain, for polymer chains with variable length. The conjugated polymers investigated here are poly(para-phenylene vinylene) (PPV) and polydiacetylene (PDA). Our results show that the energy of the excited-state increases more than that of the ground-state, as the twist angle increases up to 90º degrees. The change in the twist angle of both polymers leads to a blueshift in luminescence transition energy, the effect being stronger in PPV when the planar segments have similar sizes. The predicted blueshift in both polymers is dependent on the chain length, the effect being more pronounced for shorter-chains.